A low-profile dual-polarization programmable dual-beam scanning antenna array - Zhu, Shichao; Ning, Yuanfan; Chu, Hongbo; Xiao, Pei; Li, Gaosheng (Frontiers of information technology & electronic engineering, 2023)
Conclusions In this paper, a dual-polarization dual-beam scanning array antenna based on holographic control theory is proposed. The antenna element integrates four PIN diodes, two in each of the horizonal and vertical directions, to achieve reconfigurable polarization. By varying the states of two PIN diodes in the same direction to change the radiation phase of the element, the simulation and measurement of the 2-element subarray verify that the proposed element is capable of manipulating the radiation pattern. Based on digital coding theory, the phase-adjustable structure integrated with the PIN diodes can act as a holographic element, and the desired object wave can be accurately and stably obtained by modulating the reference wave excited by the feed and the holographic element. The simulation verifies that the antenna array can achieve satisfactory 2D beam scanning. To verify the simulation results, a 2-element subarray prototype and a 6×12 array prototype are fabricated and subjected to measurement. The results of measurement and simulation are in good agreement, which proves the feasibility of the dual-polarization dual-beam scanning antenna system. Due to its low profile, low cost, and easy integration, this antenna system excels in applications in fields such as radar systems and smart antennas.